Helicobacter pylori strains from ulcer and non-ulcer differ in binding ability to mucins - Quintana-Hayashi, M.P. (2017)
Background : Adhesion to mucins within the mucus layer and to membrane bound mucins present on the surface epithelial cells is a key step in the interacon of H. pylori and its host. Aim : To invesgate the level and mechanisms of binding of non- ulcer dyspepsia (NUD) strains versus pepc ulcer disease (PUD) strains to human gastric mucins.